Truths about the 200 Days - Roblero Rodríguez, Sonia (2004)
The debate about the length of the school year in public primary schools and high schools has become stagnant. Now, it turns out that the big question to decide is whether the school year should last 200 or 174 days as if those were magic numbers! On both sides, the legalization and the reduction of the issues to its legal gazette reach their maximum expression, which becomes absurd.